Effect of liming and free Ca2+ on Cd uptake of carrots, Daucus carota - Holmkvist, Anna (SLU/Horticulture (until 121231), 2009)
The level of cadmium (Cd) in Swedish arable land has increased during the last century and the average concentration of Cd in the plough layer is today 0.23 mg/kg. The increase is mainly due to anthropogenic activities such as phosphorus fertilizing, liming, import of feed, and atmospheric deposition from industrial emissions. Cadmium in the soil will be taken up by crops and is thereby transferred to humans via food. Carrot is one of the crops of concern, both because it may contain quite high Cd concentrations and due to the large consumption in Sweden.